1887 N.M. Laws 57, § 8 - (:unkn) unknown (My University, 1887)
Ch. 30, § 8: Defined "deadly weapons" as including pistols, whether the same be a revolved, repeater, derringer, or any kind or class of pistol or gun; any and all kinds of daggers, Bowie knives, poniards, butcher knives, dirk knives, and all such weapons with which dangerous cuts can be given, or with which dangerous thrusts can be inflicted, including sword canes, and any kind of sharp pointed canes; as also slungshots, bludgeons or any other deadly weapons.
Keywords: DEFINITIONS